The Effect of Debt to Equity Ratio, Total Assets Turnover, Current Ratio, Working Capital Turnover, and Sales Growth on Company Financial Performance - Anggraeni, Iis Arista; Kusumawati, Eny (Prosiding University Research Colloquium, 2022)
Every company must present financial statements as a true source of information. This information is useful for knowing whether the company’s financial performance is good or bad. Performance measurement can be done using a ratio measuring instrument. The purpose of this study was to examine the effect of debt to equity ratio, total aset turnover, current ratio, working capital turnover and sales growth on the financial performance of manufacturing companies in Indonesia. Indicators used to measure the company’s financial performance are debt to equity ratio, total aset turnover, current ratio, working capital turnover, and sales growth. While financial performance as the dependent variable. The sample selection method uses purposive sampling using certain criteria on the financial statements of manufacturing companies in Indonesia for the 2016-2018 period. The analytical method used is multiple linear regression analysis. The results of this study indicate that total aset turnover and working capital turnover had affect the financial performance of a company. While debt to equity ratio, curent ratio, and sales growth has no effect on the company’s financial performance.